Finger lickin' fifteen [compact disc, unabridged] - Evanovich, Janet (Evanovich, Janet. Stephanie Plum novel., 2009)
New York Times best selling author Janet Evanovich presents the fifteenth installment in the Stephanie Plum series, a collection of romantic adventures featuring the ditzy yet lovable New Jersey bounty hunter, Stephanie Plum. When Lula witnesses the murder of celebrity chef Stanley Chipotle, she teams up with Stephanie to track down the killer. However, Ranger demands Stephanie's help as well as he investigates a traitor at Rangeman who's leaking client information to the highest bidder.